Environmentally friendly protection of tea plantations in the south of Russia - E. V. Kashutina; L. N. Bugaeva; T. N. Ignateva; I. V. Heishho (Юг России: экология, развитие, 2022)
Aim. Environmentally safe protection of tea plantations in southern Russia during the revival of a previously prosperous industry and development of a strategy for the development of biological protection of tea growing in the long term which requires the integration of science and production.Material and Methods. Pest contamination of the plantation was detected during phytosanitary surveys. The number of individual pests per unit area is calculated according to the Shapiro method. Studies of the effectiveness of the Australian ladybird beetle cryptolemus (Cryptolaemus montrouzieri Muls.) in relation to tea pulvinaria were carried out on tea plantations in the Lazarevsky district of Sochi.Result. Justifications are given for the need to provide scientific support during work on farmland when developing environmentally safe protection of tea from pests and diseases. The results of surveys of tea plantations of the Black Sea coast of the Krasnodar Territory on the identification of the most dangerous pests for the yield of plantations together with the study of the effectiveness of cryptolemus in relation to tea pulvinaria (cottony camellia scale) in tea culture are given. As a result of the studies, the methodology, norms and multiplicity of the release of the cryptolaemus predator (Cryptolaemus montrouzieri Muls.) were worked out, both in the larval and imago stages, with heavily infested tea plants. The research was carried using the material and technical facilities of the unique scientific installation, State Collection of Living entomoacariphages and entomopathogens.Conclusion. The revival of tea plantations involves a set of measures aimed at increasing productivity: improving the system of cutting bushes and methods of collecting leaf, repairing, irrigating and fertilizing and mechanizing work on plantations. The use of environmentally friendly methods of protection against the most harmful objects allows the obtaining of tea raw materials of the highest quality.